METHODOLOGICAL CONDITIONS FOR FORMING ACMEOLOGICAL COMPETENCE IN FUTURE TEACHERS - Tuychieva Sabina Sherzodovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article explores the methodological conditions for forming acmeological competence in future teachers. The study focuses on the role of educational environment, pedagogical interaction, and individual learning trajectories in achieving professional excellence. Special attention is given to the integration of personality-oriented education, innovative teaching strategies, and continuous professional growth. The acmeological perspective is considered as a key framework for enhancing teacher training quality and ensuring sustainable professional development.